Control strategy with adaptive quantizer’s parameters under digital communication channels - Niu, Yugang; Ho, Daniel W.C. (Automatica (Oxford), 2014)
A stabilizing controller designed without considering quantization may not be effectively implemented for the systems with quantized information due to quantization errors. Hence, an interesting issue is how to design the quantizer such that the desired system performance can be still attained by the above controller. In this work, a new control strategy with on-line updating the quantizer’s parameter is proposed. This scheme may ensure the controlled system to attain the same dynamic performance, H∞ disturbance attenuation level, as the one without signal quantization. A practical adjusting rule on quantizer’s parameter is proposed such that the state-dependent parameter is available on both sides of encoder/decoder. Finally, some numerical examples have been provided to illustrate the present control scheme.